Program Designing the Improvement of Excavator’s Maintenance Team Competencies (Case Study in a Sandstone Mine Company PT XYZ) - Agung Aribowo; Nani Kurniati (Institut Teknologi Sepuluh Nopember, 2019)
The heavy equipment maintenance system cannot be separated from the problems of Human Resources (HR). Some literature has defined HR as a success factor for the successful implementation of maintenance systems. The Asset Maintenance Division as an organization which responsible to maintain the Company's assets routinely, including the Doosan S500’s 50-tonne class excavator. But in fact, excavators that are currently still operated often breakdown and its physical condition are in a bad condition. From the observation of 9 (nine) units excavators, the Key Performance Indicator (KPI) target was still not achieved, especially on the items Mean Time To Repair (MTTR) and Mean Time Between Failure (MTBF). Mechanic’s technical competencies needed in achieving KPI are divided into four sub competencies: Maintenance, Repair & trouble shooting, Remove & install and Overhaul. This study aims: analyzing mechanic’s competencies against company‘s standards, analyzing the influence of mechanic’s competencies on achieving KPI targets, providing recommendations on the influence of mechanic’s competencies for achieving KPI targets. The primary data used in the study were obtained through interviews and the questionnaires as well as secondary data obtained from various literatures, research results and supporting books. The method of processing and analyzing data uses the method of gap analysis and the Non-Parametric Statistics (Multiple Regression). The results of the gap analysis are known that there are still gaps in the actual competence of employees with competency standards set by the company. Factors that cause the competency gap are generally known because of a lack of understanding of the basic skills required, mastery of work techniques and consistency in applying work quality standards. Recommendations from this study as an effort to improve the skills and knowledge of mechanics to improve work effectiveness that affects MTTR and the quality of work that affects MTBF so that the KPI are consistently achieved